Influence of Vagus Nerve Stimulation parameters on chronotropism and inotropism in heart failure - Rousselet, Laure; Le Rolle, Virginie; Ojeda, David; Guiraud, David; Hagege, Albert; Bel, Alain; Bonnet, Jean-Luc; Mabo, Philippe; Carrault, Guy; Hernandez, Alfredo I. (2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society, 2014)
Vagus Nerve Stimulation (VNS) has been shown to be useful in heart failure patients, including antiarrhythmic effects, improvement of cardiac function and reduction of the mortality. However, the optimal configuration of VNS can be a difficult task, since there are several adjustable parameters, such as current amplitude (mA), pulse width (ms), burst frequency (Hz), number of pulses and, in the case of cardiac-triggered VNS, the delay (ms) between the R-wave and the beginning of the stimulation. The objective of this paper is to analyse the effect of these parameters, and their interaction, on the chronotropic and inotropic responses to vagal stimulation. 306 VNS sequences were tested on 12 sheep with induced heart failure. Autonomic markers of the chronotropic (changes in RR interval) and inotropic (changes in dP/dt max ) effects were extracted from the observed data. In order to analyse the influence of stimulation parameters on these markers, a sensitivity analysis method was applied. Results illustrate the strong interaction between the delay and the others parameters. The number of pulses, the current and the frequency seem to be particularly influent on chronotropism and inotropism although the effect of the frequency is highly non-linear or it depends on other parameters.